(untitled) (Journal of Advanced Research in Social Sciences, 2020)
The Lok Sabha Elections 2019 in the world’s largest democracy, India, was the biggest electoral event on the planet. These elections are key in the selection of the Prime Minister, the highest authority in the cabinet. Keeping in pace with the global trend, the Indian elections saw a very prominent use of Online Social Media by political parties to create a major discourse around the event. We focus our study on Twitter, collecting over 45 Million tweets, tracking more than 3500 hashtags and over 2500 political handles while monitoring their network interactions. In this work, we have analysed tweets from all these political handles to see how narratives were shaped and altered over time. We study these narratives formed by the party already in power and how they were supported or challenged by other parties. Spanning over 5 months, January to May 2019, we analysed the monthly changes in the rhetoric created by the leading political parties and leaders. We then discern the impact of these changes on existing narratives during the campaigning and the elections.